Preliminary study of resistance in 4 populations of Helopeltis theobromae Miller (Hemiptera: Miridae) to γ − HCH, Propoxur and Dioxacarb. - Omar, Dzolkhifli; Khoo, Khay Chong; Muhamad, Rita
Four populations of Helopeltis theobromae Miller were investigated in Peninsular Malaysia for the existence of resistance to alpha-HCH, propoxur and dioxacarb by means of time-response assays. The insects were confined on treated filter paper and time to knockdown was recorded to establish lethal exposure time (LT50) and percentage survival. The order of sensitivity of different populations to alpha-HCH was Serdang Bagan Datoh Teluk Intan Intan = Kajang; and to dioxacarb, Serdang Kajang was consistently most sensitive or susceptible to all three insecticides. The Kajang population the only one showing tolerance or resistance, having an LT50 value three times higher than the Serdang population; the survival after 4 hr continuous exposure was 36% for the former and nil for the latter. The existence of differential sensitivity to each of the three insecticides between the four populations indicated an impending resistance problem.